Imaging analysis 3D cone-beam computed tomography of a suspected infected radicular cyst in the mandible - Merry Annisa Damayanti; Ria Noerianingsih Firman; Fahri Reza Ramadhan; Ika Rachmawati; Fadhlil Ulum Abdul Rahman; Aga Satria Nurrachman; Norlaila Sarifah; Alongsyah Zulkarnaen Ramadhan; Indra Gunawan (Ikatan Radiologi Kedokteran Gigi Indonesia, 2022)
Objectives: This article is aimed to report the use of cone-beam computed tomography (CBCT) imaging analysis on a radiolucent lesion case. Case Report: A 24-year-old female patient was referred to dentomaxillofacial radiology installation, at Universitas Padjadjaran Dental Hospital for a CBCT examination of a lower jaw lesion. The CBCT result demonstrated a large radiolucent lesion at the periapical of tooth 37 with a mostly diffuse border that extended posteriorly to the ramus. There was a cortical thinning on the lingual side alveolar bone. Density analysis revealed an average density of –22,9 grayscale. Conclusion: CBCT 3D could analyze lesions from qualitative and quantitative approaches. Based on these approaches, the lesion of this case led to a suspect of infected radicular cyst.